Indicadores objetivos e subjetivos de qualidade de vida das famílias brasileiras segundo a POF de 2002-2003: Um estudo sobre seus determinantes demográficos, sociais e econômicos - Marcelo de Sales Pessoa; Marco Antonio C. da Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper uses an ordered logit model to investigate the demographic, economic and social determinants of the performance of some partial life quality indicators for Brazilian households, based on the POF 2002-2003 survey on life conditions evaluation. Some indicators have a subjective content, which measure the degree of households' satisfaction with some important aspects of their life conditions. The study emphasizes the comparative analysis between the effects of current income and permanent income on the indicators. In this aspect, it turns out that the estimated effect of permanent shocks on current income is stronger than that of temporary shocks. Another relevant result is the low joint explanation power of income and consumption, notwithstanding their significant effect on the indicators' performance. This result is consistent with the international empirical evidence of a mismatch between objective and subjective life quality indicators, which can be explained to some extent by differences in expectations and perceived relative income among households. The inclusion of an exhaustive number of explanatory variables into the model-in addition to income and consumption-increases its explanatory power, but not to a large enough extent to produce a satisfactory adjustment to the data. This fact suggests the existence of some type of non-observed heterogeneity explaining a fairly amount of the Brazilian life quality indicators' performance.
Keywords: I30; I31; I39; 330